2001
DOI: 10.1080/00036840150203297
|View full text |Cite
|
Sign up to set email alerts
|

Price transmission analysis: a flexible methodological approach applied to European pork and lamb markets

Abstract: The study of spatial price relationships contributes to explain markets performance, their degree of integration or isolation, and the speed at which information is transmited. A great deal of methods have been used to analyze this issue, being the most important: causality tests, impulseresponse functions and cointegration. Normally, these techniques have been individually applied. However, a more rich knowledge of markets performance can be extracted when they are jointly applied. In this paper, we try to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 0 publications
0
20
0
7
Order By: Relevance
“…A number of applied analyses on spatial price transmission have focused their attention on food markets (Goodwin and Piggott, 2001;Zanias, 1993). While most previous studies have been based on U.S. (Goodwin and Piggott, 2001) or international data (Dries and Unnevehr, 1990), European food markets have received less attention (Zanias, 1993;Gordon, Hobbs and Kerr, 1993;Sanjuán and Gil, 2001 are a few exceptions). Additionally, to our knowledge, no published study has addressed EU spatial food price relationships after the implementation of the Single Market in 1993, which involved the removal of barriers to trade within the EU.…”
Section: Introductionmentioning
confidence: 99%
“…A number of applied analyses on spatial price transmission have focused their attention on food markets (Goodwin and Piggott, 2001;Zanias, 1993). While most previous studies have been based on U.S. (Goodwin and Piggott, 2001) or international data (Dries and Unnevehr, 1990), European food markets have received less attention (Zanias, 1993;Gordon, Hobbs and Kerr, 1993;Sanjuán and Gil, 2001 are a few exceptions). Additionally, to our knowledge, no published study has addressed EU spatial food price relationships after the implementation of the Single Market in 1993, which involved the removal of barriers to trade within the EU.…”
Section: Introductionmentioning
confidence: 99%
“…As Sanjuán and Gil (2001) underlined, applying one method of analysis may not be flexible enough to account for the complex interactions of prices in separated markets. Nevertheless, our methodology can be seen as a first step in an ongoing analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This was, for instance, the conclusion of Sanjuán and Gil (2001) for the EU pork and lamb markets in the period 1988-1995 and of Serra et al (2006) in the case of the EU pork market in the period 1994-2004Tangermann (1992) analysed price relationships across Member States in the period 1974-89. He found that differences between prices and price variation in years 1987-89 increased in comparison with years 1974-76 which he interpreted as a sign of market deterioration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Valgan como ejemplo los estudios sobre el mercado del arroz (Silvapulle y Jayasuriya, 1994), los cereales (Gil et al, 1996), el maíz (Abdulai, 2000), la carne de cerdo y cordero (Sanjuan y Gil, 2001), el algodón (Baffes y Ajwad, 2001), las hortalizas de invernadero (Martínez-Carrasco, 2004), el pescado blanco en Europa (Nielsen, 2005) o el mercado internacional del azúcar (Alonso y Arcila, 2012). Entre los trabajos citados se encuentran las principales aplicaciones del estudio de integración de precios y mercados a productos agroalimentarios en España.…”
Section: Materials Y Métodosunclassified